Comparison of the effects of octreotide and melatonin in preventing nerve injury in rats with experimental spinal cord injury - Erol, Fatih S.; Kaplan, Metin; Tiftikci, Murat; Yakar, Huseyin; Ozercan, Ibrahim; Ilhan, Necip; Topsakal, Cahide (Elsevier Sci Ltd, 2008)
In this study, we aimed to investigate the biochemical and histopathological protective effects of octreotide and melatonin in an experimental model of spinal cord injury. Fifty-six male albino Wistar rats were divided into four groups. Rats in the G1 group (n = 7; control group) did not undergo any treatment except for anesthesia prior to being killed. Rats in the G2 group (n = 7) underwent laminectomy and aneurysmal clip application at the T4-5 level. G3 group rats (n = 14) were either treated with a 7.5 mg/kg intraperitoneal dose of melatonin (Sigma, St. Louis, MO, USA) immediately after laminectomy, then the same dose again on the day following injury (G3a), or given three equal doses over 10 days to achieve a total dose of 7.5 mg/kg/day (G3b). G4 group rats (n = 14) were either treated with a 30 mu g/kg intraperitoneal dose of octreotide (Sandostatin; Novartis, Istanbul, Turkey) immediately after laminectomy, then the same dose again on the day following injury (G4a), or given three equal doses over 10 days to achieve a total dose of 30 mu g/kg/day (G4b). Rats in the G3 and G4 groups were sacrificed on days I and 10 after spinal cord injury (n = 7 at each time point) and spinal cord samples were obtained. Tissue malonyldialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) levels were assayed. G3a, G3b and G4b had significantly lower levels of MDA than G2 (p < 0.01). G3b had significantly higher SOD and GSH-Px levels than G2 (p < 0.01). Histopathologically, melatonin significantly reduced necrosis and degeneration in both the initial and late stages (p < 0.01). Octreotide had significant effects on necrosis and degeneration during the late stages, and on edema and congestion in both the initial and the late stages of injury (p < 0.01). Melatonin was found to be superior to octreotide with respect to the prevention of congestion, edema, axonal degeneration and necrosis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: histopathology; lipid peroxidation; melatonin; octreotide; spinal cord injury